Alternative internal splicing in c-myb RNAs occurs commonly in normal and tumor cells. - Shen-Ong, G L (1987)
Activation of the c-myb gene by viral transduction or proviral insertional mutagenesis that is likely to result in the production of structurally altered myb proteins has been shown to be predominantly associated with myelomonocytic tumors. An alternative splicing event in which a portion of the intron bounded by the vE6 and vE7 exons with v-myb homology is included as an additional 363-nucleotide coding exon has recently been identified in a mouse tumor that carries a provirus-activated myb gene. This alternative splicing was hypothesized to be a tumor-specific aberrant form of 3'-myb RNA processing as a consequence of the disruption of upstream 5'-sequences by proviral insertion. However, RNA blot analyses and RNase mapping studies presented here show that a significant portion (approximately 10%) of all myb transcripts examined, whether in normal or in clonal tumor cells, contains the additional exon. Hence the alternative splicing is a hitherto unrecognized common normal event that potentially increases the diversity of the myb proteins expressed in normal tissues including thymus and spleen, as well as in tumor cells with either normal or 5'-rearranged myb alleles. The lack of change in the ratio of the two spliced products expressed from either the normal or the 5'-rearranged myb further indicates that the insertion of the unique 121 amino acids in the larger myb transcripts is not a consequence of tumor-specific activation of the mouse myb oncogene.